(3eSfO GHf CHj TjHIs - (3CHh HcQ YHO Gddg Hf eMeO Hf CHj TjHI GdYHSj, GHf CHj TjHI,J (B235 (3g` s
(3ChdgG (B:s
(3MOjK HfjW Hf TQjW bGd CNHQfG CMeO Hf NGdO , bGd (B: (3CNHQfG eMeO Hf hVGM , QCjJ QShd Gddg Udi Gddg Ydjg hSde jNWH Ydi HYjQ s
(3BNQgG (B:s
(3Yf GdfHi Ydjg GdSdGe , bGd (B: (3EPG OYGc GdOGYjGf aCLH CbQHgeG HGHkG aEf CbQHgeG HGHG CbQHgeG LhGRkG , hEf LGA GLejYkG aCLH GdPi SHb Je MOjK GdeTGjN s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ gPg GdfSNI Ydi Qb GdZRGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B117s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs